Late History of Cattle Breeds in Central Europe in Light of Genetic and Archaeogenetic Sources-Overview, Thoughts, and Perspectives - Janák, Vojtěch; Novák, Karel; Kyselý, René (Animals, 2024)
Although Europe was not a primary centre of cattle domestication, its expansion from the Middle East and subsequent development created a complex pattern of cattle breed diversity. Many isolated populations of local historical breeds still carry the message about the physical and genetic traits of ancient populations. Since the way of life of human communities starting from the eleventh millennium BP was strongly determined by livestock husbandry, the knowledge of cattle diversity through the ages is helpful in the interpretation of many archaeological findings. Historical cattle diversity is currently at the intersection of two leading directions of genetic research. Firstly, it is archaeogenetics attempting to recover and interpret the preserved genetic information directly from archaeological finds. The advanced archaeogenetic approaches meet with the population genomics of extant cattle populations. The immense amount of genetic information collected from living cattle, due to its key economic role, allows for reconstructing the genetic profiles of the ancient populations backwards. The present paper aims to place selected archaeogenetic, genetic, and genomic findings in the picture of cattle history in Central Europe, as suggested by archaeozoological and historical records. Perspectives of the methodical connection between the genetic approaches and the approaches of traditional archaeozoology, such as osteomorphology and osteometry, are discussed. The importance, actuality, and effectiveness of combining different approaches to each archaeological find, such as morphological characterization, interpretation of the historical context, and molecular data, are stressed.
Keywords: historical cattle; osteometry; hornlessness; sexual dimorphism; aurochs; Czech Red cattle; archaic DNA